Impact of a Conducive Office Physical Environment on the Productivity Level of Bestlink College of the Philippines’ Accounting Department: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The productivity of an organization's workforce has a significant role in its performance,which determines its survival and growth. Organizations nowadays have a lot of unattendedissues relating to employee productivity. One of these issues is the inability to guarantee andgive a positive and suitable work environment for the employees. The physical features ofthe workplace are just as important in maintaining expected labor productivity. This researchstudy is raised to investigate how a conducive office physical environment impactsemployee’s motivation and productivity.The majority of employees acknowledge that their present workplace's physical environmenthas a significant impact on their level of productivity and motivation to perform. Additionally,the employees perceived that there were serious problems with office layout, deskmanagement, ventilation, workspace, ergonomics, and document storage capacity. It alsorevealed that there are unlabeled documents, cabinets, and drawers, or they containundetectable information that is difficult to recognize and causes it to be inefficient, andfinding documents or files, whether they be in physical or digital format, is a problem in theworkplace.The results demonstrated that an organization needs to enhance its physical workingenvironment in order to persuade people to remain in the office and be productive. Theresearchers recommend that Bestlink College of the Philippines' Accounting Departmentimprove its office layout by implementing the 5S system for office management (sort, set inorder, shine, standardize, and sustain). These procedures entail going over each object in aroom, evaluating what is and isn't necessary, organizing everything, cleaning, andestablishing protocols for executing these duties on a regular basis.
Keywords: Business Administration